PESANTRENPRENEUR SEBAGAI GERAKAN PEMBANGUNAN EKONOMI MASYARAKAT LOKAL - Kurniawan, Muhammad Arif; Pramadeka, Katra (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2024)
Pesantrenpreneur has great potential to not only strengthen the role of pesantren as an educational institution, but also as a motor for local economic development. This research aims to reveal in detail how pesantrenpreneur movement at the Islamic Boarding School (pesantren) of Lintang Songo is used as a development of pesantren economy and to find out what strategies of Pesantren Lintang Songo has in driving the existence of its pesantrenpreneurs. This research is a qualitative study with a case study approach. Data collection using observation, structured interviews and documentation, while the data analysis technique used is the Miles and Huberman model analysis. The research results indicate that Pesantren Lintang Songo has carried out various stages of pesantrenpreneurship well, including: 1) Pesantren internship stage, 2) Pesantren launch stage, 3) Pesantren take-off stage and 4) Pesantren maturity stage. Not only that, this pesantren also has four strategies to drive its existence in the wider community, including: 1) collaborating with the local community to manage agriculture and plantations, 2) recruiting assistants from students for various pesantren productions, 3) collaborating with the local government in providing assistance to improve the skills of students in pesantren entrepreneurship and 4) renting community land to be used as productive land. The impact of pesantrenpreneurs at Pesantren Lintang Songo is greatly felt by the students and the community, especially in the development of the local community economy.